Inclusion of older adults and reporting of consent processes in randomized controlled trials in the emergency department: A scoping review - Lauren T Southerland; Katherine K. Benson; Austin J. Schoeffler; Margaret A. Lashutka; Soo Borson; Jason J. Bischof (Journal of the American College of Emergency Physicians Open)
Abstract Objective Conducting research in the emergency department (ED) is often complicated by patients’ acute and chronic illnesses, which can adversely affect cognition and subsequently capacity to consent for research, especially in older adults. Validated screening tools to assess capacity to consent for research exist, but neither the frequency of use nor which ones are used for ED research are known. Methods We conducted a scoping review using standard review techniques. Inclusion criteria included (1) randomized controlled trials (RCTs) from publication years 2014–2019 that (2) enrolled participants only in the ED, (3) included patients aged 65+ years, and (4) were fully published in English. Articles were sourced from Embase and screened using Covidence. Results From 3130 search results, 269 studies passed title/abstract and full text screening. Average of the mean or median ages was 55.7 years (SD 14.2). The mean number of study participants was 311.9 [range 8–10,807 participants]. A few (n = 13, 4.8%) waived or had exception from informed consent. Of the 256 studies requiring consent, a fourth (26.5%, n = 68) specifically excluded patients due to impaired capacity to consent. Only 11 (4.3%) documented a formal capacity screening tool and only 13 (5.1%) reported consent by legally authorized representative (LAR). Conclusions Most RCTs enrolling older adults in EDs did not report assessment of capacity to consent or use of LARs. This snapshot of informed consent procedures is potentially concerning and suggests that either research consent processes for older patients and/or reporting of consent processes require improvement.